2021
DOI: 10.1039/d1nr00001b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon contamination in angström-scale channels

Abstract: Air-borne hydrocarbon contamination is investigated for slit-like angstrom-channels made from 2D-materials, using gas flow measurements. Our results constitute a new way to monitor, assess and alleviate the hydrocarbon contamination in nanochannels.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…The interactions of liquid water with graphite, graphene and, in general, hydrophobic 2D materials have many features in common, 16,17 therefore, these findings should be also applied to nanopore devices that involve 2D material-aqueous interfaces. 39 In summary, real-time and atomic-scale depth resolution images demonstrated that the interfacial water structure on pristine graphite surfaces transitioned from hydration to hydrocarbon layers. Free energy minimization drives the transfer of hydrocarbons, in particular, alkane-like molecules from the gas phase through water to adsorption on graphite surfaces.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The interactions of liquid water with graphite, graphene and, in general, hydrophobic 2D materials have many features in common, 16,17 therefore, these findings should be also applied to nanopore devices that involve 2D material-aqueous interfaces. 39 In summary, real-time and atomic-scale depth resolution images demonstrated that the interfacial water structure on pristine graphite surfaces transitioned from hydration to hydrocarbon layers. Free energy minimization drives the transfer of hydrocarbons, in particular, alkane-like molecules from the gas phase through water to adsorption on graphite surfaces.…”
Section: Discussionmentioning
confidence: 93%
“…The interactions of liquid water with graphite, graphene and, in general, hydrophobic 2D materials have many features in common, 16,17 therefore, these findings should be also applied to nanopore devices that involve 2D material-aqueous interfaces. 39…”
Section: Discussionmentioning
confidence: 99%
“…16 In fact, when nanochannels are reduced to angstrom sizes, clogging occurs from contamination adhering to them. 17 At the angstrom scale, the interaction between contaminants and the nanochannel wall becomes more significant. Adsorption of contaminants onto the wall of the nanochannel occurs as a result of this interaction, which hinders the permeation of fluid in the channel.…”
mentioning
confidence: 99%
“…To gain deeper physical insight into the clogging mechanism and to be able to explain the recent experiment, 17 we calculated the energy barrier for the hydrocarbon to enter the nanochannel as a function of the width of the 2D channel. Once inside the channel, we obtained the diffusion barrier for the hydrocarbon to move inside the channel.…”
mentioning
confidence: 99%
See 1 more Smart Citation